A Review of Therapies for Clostridioides difficile Infection - Faiza Morado; Neha Nanda (Antibiotics, 2024)
Clostridioides difficile is an urgent public health threat that affects approximately half a million patients annually in the United States. Despite concerted efforts aimed at the prevention of Clostridioides difficile infection (CDI), it remains a leading cause of healthcare-associated infections. CDI is associated with significant clinical, social, and economic burdens. Therefore, it is imperative to provide optimal and timely therapy for CDI. We conducted a systematic literature review and offer treatment recommendations based on available evidence for the treatment and prevention of CDI.